Detection of oxidative hair treatment using fluorescence microscopy. Issue 8 (11th September 2015) - Witt, Silvana; Wunder, Cora; Paulke, Alexander; Verhoff, Marcel A.; Schubert‐Zsilavecz, Manfred; Toennes, Stefan W.
Abstract : In assessing abstinence from drug or alcohol abuse, hair analysis plays an important role. Cosmetic hair treatment influences the content of deposited drugs which is not always detectable during analysis. Since oxidation of melanin leads to an increase in fluorescence, a microscopic method was developed to distinguish natural from cosmetically treated hair. For validation, natural hair samples were treated with different types of cosmetics and inspected by fluorescence microscopy. Hair samples from 20 volunteers with documented cosmetic treatment and as a proof of concept 100 hair samples from forensic cases were analyzed by this method. Apart from autofluorescence with excitation at 365 nm, no obvious fluorescence was observed in untreated hair samples. Tinting and a natural plant product had no influence on fluorescence, but dyeing procedures including oxidation led to a marked increase in fluorescence. Proof of cosmetic treatment was achieved in hair samples from the 20 volunteers. In 100 forensic cases, 13 samples were characterized as oxidatively treated, which was in accordance with the respective disclosure except for one case where treatment was not admitted. This fluorescence microscopic procedure proved to be fast, easy, and reliable to identify oxidatively treated hair samples, which must be considered especially in evaluating cases of negative drug results. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : In abstinence control, detectability of drugs of abuse or ethyl glucuronide is hampered in oxidatively treated hair which may go unnoticed during analysis. However, in forensic cases this must be considered, especially in the evaluation of negative analysis results. The present study describes a simple and efficient method for identification of such hair samples via fluorescence microscopic inspection of a single hair.